2018
DOI: 10.1021/acs.molpharmaceut.8b00547
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Uptake of the Atypical Antipsychotic Clozapine Is a Carrier-Mediated Process

Abstract: The weak base antipsychotic clozapine is the most effective medication for treating refractory schizophrenia. The brain-to-plasma concentration of unbound clozapine is greater than unity, indicating transporter-mediated uptake, which has been insufficiently studied. This is important, because it could have a significant impact on clozapine's efficacy, drug-drug interaction, and safety profile. A major limitation of clozapine's use is the risk of clozapine-induced agranulocytosis/granulocytopenia (CIAG), which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 76 publications
2
17
0
Order By: Relevance
“…K p,uu values larger than unity could indicate active uptake transport of olanzapine across the BBB in the rodent animal models. This is corroborated by a report by Dickens et al, who found that clozapine, a second-generation antipsychotic structurally similar to olanzapine, was actively taken up by the human brain endothelial cell line hCMEC/D3 [32]. It is therefore not unlikely that the discrepancy between in vitro observation of efflux transport of olanzapine and K p,uu values larger than unity in animal models can be explained by active uptake processes outcompeting potential weak efflux transport, rather than species differences.…”
Section: Bidirectional Transport Of Selected Model Drugs Was Not Diffsupporting
confidence: 71%
“…K p,uu values larger than unity could indicate active uptake transport of olanzapine across the BBB in the rodent animal models. This is corroborated by a report by Dickens et al, who found that clozapine, a second-generation antipsychotic structurally similar to olanzapine, was actively taken up by the human brain endothelial cell line hCMEC/D3 [32]. It is therefore not unlikely that the discrepancy between in vitro observation of efflux transport of olanzapine and K p,uu values larger than unity in animal models can be explained by active uptake processes outcompeting potential weak efflux transport, rather than species differences.…”
Section: Bidirectional Transport Of Selected Model Drugs Was Not Diffsupporting
confidence: 71%
“…Although this view remains controversial, even hydrophobic molecules do not normally 'float across' whatever phospholipid bilayer portion of cells may be untrammelled by proteins. Xenobiotics in particular need to 'hitchhike' on protein transporters that have presumably evolved for 'natural' substrates but that are capable of their uptake (142)(143)(144)(145)(146)(147)(148)(149)(150)(151)(152) . While transporters seem to have remained somewhat understudied (153) , those transporters involved in uptake and encoded by the human genome are now catalogued formally as SLC for solute carriers (154,155) , with efflux transporters mainly being classed as ABC families (156) .…”
Section: Slc22a4: the Ergothioneine Transportermentioning
confidence: 99%
“…5B) and lamotrigine (10 µM, Fig. 5C)(25) to determine if OCT3 is required for NE-stimulated intracellular PI4P hydrolysis.Preincubation of NRVMs with any of these inhibitors prevented NE from inducing PI4P hydrolysis, suggesting that OCT3-mediated transport is required for PI4P hydrolysis by this catecholamine. In addition, we sought to determine if receptor internalization is required for NE-mediated PI4P hydrolysis and bAR activation at the Golgi.…”
mentioning
confidence: 99%